PENGARUH KEGIATAN PENAMBANGAN EMAS TERHADAP PLANKTON DAN KUALITAS AIR SUNGAI ANSOTOK DI KABUPATENPONTIANAK (The Influence of Gold Mining on Plankton and Water Quality of Ansotok River in Pontianak Regency) - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Farmasi UGM, 2000)
ABSTRACT The aims of this research were (1) to examine the influence of gold mining on plankton and water quality (2) to understand the relationships between water quality parameter (physical, chemical, and biological parameter) and the location, and (3) to understand the degree of the river pollution of the Ansotok River in Pontianak Regency. The sampling was carried out purposively, employing 15 stations with 2 replications to represent all the research area. Samples of plankton were obtained from 15 stations, on the left side, in the middle, and on the right side of the river for each station. The procedure adopted in this sampling was by taking 100 liters of water which was distilled into 15 cc and preserved in a solution of 1 cc forma lin. The plankton samples were analysed in the laboratory to establish the genus, population, and diversity index of plankton. Water samples were taken from the affore side 15 stations. From each observation site, 9 liters of water was taken and mixed, and then 1 liter of this mixture was analysed in the laboratory to establish the total dissolved solid, turbidity and mercury contents, whereas the spatial and ecological approaches were used throughout the research. The degree of river water pollution due to gold mining was based on diversity index of plankton, and water quality was based on the B category. The correlation analysis was used to reveal the relationship between physical, chemical, and biological measurement standards, in one hand, and gold mining location, on the other hand. The linear regression was used to predict the influence of the distance from the activity location on the river quality. Spatial analysis was used to investigate diversity index of plankton distribution and water quality parameters. The result of this research showed the following (1) gold mining activity had negative influence on plankton life only at waste channel due to its high degree of mercury contents and turbidity, (2) the diversity index of plankton started getting betterat the distance of Â± 405 meters form the location (Keronang), (3) water quality started getting better at the distance of Â± 405 meters form the location (Keronang), and (4) the water quality in Ansotok River, as raw material for drinking water based on its usage, and diversity index plankton was categorized as unpolluted.